Prinsepia utilis Royle: An Unexplored Treasure for the Livelihood Enhancement in Himalaya Hills - Kumar, Prabal; Kumar, Aman; Kumar, Devendra; Singh, Sanjay; Kumar, Abhishek (Indian Forester, 2023)
Prinsepia utilis Royle, commonly known as Bhekal, Bekhal or Bekoi, is a moderate-sized perennial woody shrub frequently occurring throughout the Himalaya hills in altitudes of 1000 to 3000 m asl. To conduct the scientific study and documentation of the indigenous traditional knowledge related to P. utilis Royle are the main objective of this study. Several ethnobotanical surveys were carried out from July 2016 to June 2018 to achieve this goal. The study revealed several traditional usages as a potential source of edible oil, fuel, fodder and medicines and in many ritualistic practices. Despite the extraordinary potential benefits of P. utilis in the socio-economics of people of this region, the diminished interests in its utilisation have led to poor conservation and depletion of its genetic resources. Owing to its multi-purpose benefits and usages, it can be a highly promising plant for the upliftment of the socio-economic status of the native peoples living in Jaunsar-Bawar region of the Himalaya. The underutilized tremendous economic potential of this plant can be harnessed by encouraging commercial cultivation of P. utilis for its oilseeds. The businesses related to oilseed collection, processing and oil extraction can flourish and improve the socioeconomic status of this region. To maintain this knowledge, comprehensive approach and collaboration are needed to maintain historical records on traditional knowledge in favour of human beings, before they are destroyed forever. Therefore, a summary of the taxonomy, the contemporary traditional use of the plant/ plant parts and products, based on field survey from Chakrata, Uttarakhand has been documented in this paper.